DVTC-Based Series RL/RC Impedance Simulator - Nutcha Likhitkitwoerakul; Natchanai Roongmuanpha; Worapong Tangsrirat (My University, 2021)
In this study, a grounded impedance simulator employing differential voltage to current converter (DVTC) as an active element is presented. The proposed circuit consists of two DVTCs along with three passive elements. By properly selecting the three passive elements, the series RL and RC impedance can be simulated. The simulated equivalent resistance, inductance and capacitance values can be accessed by selecting the values of the passive elements. To confirm the workability of the proposed simulator, simulation results in comparison with the theoretical finding have been presented. Second-order current mode lowpass-and highpass-filters are performed as application examples to prove the performance of the proposed simulator.
Keywords: Analog and Mixed-Signal Circuit Design; Radio Frequency Integrated Circuit Design; Innovative Energy Harvesting Technologies